2019
DOI: 10.3390/ani9050227
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of Fat-Based Energy Supplement to Light Birth Weight Pigs Shortly After Birth Does Not Increase Their Survival and Growth

Abstract: Low birth weight piglets are at high risk of mortality, because of the rapid depletion of their energy reserves after birth. At 3 h postpartum, 405 piglets weighing <1.1 kg were either dosed orally with 2 mL of (1) coconut oil (CO, 74 kJ/2 mL, n = 107 piglets), (2) commercial product (CP, 71 kJ/2 mL, n = 101 piglets), (3) water (W, 0 kJ/2 mL, n = 100 piglets) or (4) were sham-dosed (S, n = 97 piglets). Treatments were applied within litter (97 sows). Before treatment piglets were weighed, scored for vitalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 35 publications
1
27
1
Order By: Relevance
“…Additionally, once the uterus has surpassed normal limits of uterine space, every additional littermate is associated with a reduction in individual fetal growth [16,17]. In turn, larger litters are strongly correlated with a proportion of piglets born underweight (<1.0 kg) [8,10]. Observing the performance of 965 litters, Quiniou et al [7] found that larger litters had a 33 g decrease in mean birth weight average over 'normal' litters at 11 pigs.…”
Section: Intrauterine Crowding and Its Impact On Piglet Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, once the uterus has surpassed normal limits of uterine space, every additional littermate is associated with a reduction in individual fetal growth [16,17]. In turn, larger litters are strongly correlated with a proportion of piglets born underweight (<1.0 kg) [8,10]. Observing the performance of 965 litters, Quiniou et al [7] found that larger litters had a 33 g decrease in mean birth weight average over 'normal' litters at 11 pigs.…”
Section: Intrauterine Crowding and Its Impact On Piglet Developmentmentioning
confidence: 99%
“…As advances in genetics [1][2][3], reproductive management [4], and nutrition [5,6] continue to increase the number of piglets a sow can produce per litter [7,8], it is important to consider the issues that are associated with larger litters, particularly surrounding piglets and pre-weaning survival. Issues surrounding large litters include the effects of intrauterine crowding and so birth weight variation, piglet hypoxia during delivery and litter-mate competition post-partum.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Muns et al [12] found that giving light birth weight piglets (<1.35 kg) a commercial product consisting mainly of glycerol and colostrum replacer decreased mortality rate the first 24 h after birth and mortality rate until day 21 in lactation, respectively. In contrast, Schmitt et al [21] found that giving low birth weight piglets (<1.1 kg) coconut oil and a commercial product consisting mainly of fat did not affect survival rate or BW gain during lactation. The studies gave different doses of supplement (3 g in Declerck et al [13]; 2 × 1 and 5 mL in Muns et al [12]; 2 mL in Schmitt et al [21]) equaling to different approximate total amount of energy (163 kJ in Declerck et al [13]; 32 kJ and 83 kJ in Muns et al [12]; 71 kJ in Schmitt et al [21]).…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, Schmitt et al [21] found that giving low birth weight piglets (<1.1 kg) coconut oil and a commercial product consisting mainly of fat did not affect survival rate or BW gain during lactation. The studies gave different doses of supplement (3 g in Declerck et al [13]; 2 × 1 and 5 mL in Muns et al [12]; 2 mL in Schmitt et al [21]) equaling to different approximate total amount of energy (163 kJ in Declerck et al [13]; 32 kJ and 83 kJ in Muns et al [12]; 71 kJ in Schmitt et al [21]). In comparison, the present study gave a higher dose of supplement to GLUC12 piglets (2 × 12 mL), however, this equals to a lower total amount of energy (19 kJ).…”
Section: Discussionmentioning
confidence: 89%
“…At 10 days post farrowing, creep feed was introduced to habituate the piglets to post-weaning solid feeding. Details of the sow diets and creep feed given to piglets during lactation can be found in Schmitt et al [ 14 ].…”
Section: Methodsmentioning
confidence: 99%